2021
DOI: 10.1038/s41419-021-04176-8
|View full text |Cite
|
Sign up to set email alerts
|

USP7 facilitates SMAD3 autoregulation to repress cancer progression in p53-deficient lung cancer

Abstract: USP7, one of the most abundant ubiquitin-specific proteases (USP), plays multifaceted roles in many cellular events, including oncogenic pathways. Accumulated studies have suggested that USP7, through modulating the MDM2/MDMX-p53 pathway, is a promising target for cancer treatment; however, little is known about the function of USP7 in p53-deficient tumors. Here we report that USP7 regulates the autoregulation of SMAD3, a key regulator of transforming growth factor β (TGFβ) signaling, that represses the cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Based on the Ub chain, Ub modifications could be classified into monoubiquitination (substrate protein tagged with a single Ub molecule) and polyubiquitination (substrate protein tagged with a multiple Ub molecule), and according to the Ub binding sites, ubiquitination are accordingly named K6-, K11-, K27-, K29-, K23-, K48-, and K63linked ubiquitination [36] . Importantly, USP7 can hydrolyze almost all types of Ub through monoubiquitination as well as K48-and K63-linked polyubiquitination [10,37] . Furthermore, USP7 has been shown to markedly reduce the polyubiquitination levels of the substrate proteins, thereby exerting diverse functions [20,38,39] .…”
Section: Usp7 Regulates Diverse Types Of Ubiquitinationmentioning
confidence: 99%
“…Based on the Ub chain, Ub modifications could be classified into monoubiquitination (substrate protein tagged with a single Ub molecule) and polyubiquitination (substrate protein tagged with a multiple Ub molecule), and according to the Ub binding sites, ubiquitination are accordingly named K6-, K11-, K27-, K29-, K23-, K48-, and K63linked ubiquitination [36] . Importantly, USP7 can hydrolyze almost all types of Ub through monoubiquitination as well as K48-and K63-linked polyubiquitination [10,37] . Furthermore, USP7 has been shown to markedly reduce the polyubiquitination levels of the substrate proteins, thereby exerting diverse functions [20,38,39] .…”
Section: Usp7 Regulates Diverse Types Of Ubiquitinationmentioning
confidence: 99%
“…Also, in LUAD cell lines, inactivation of USP7 induces sensitivity of paclitaxel and docetaxel through degradation of Ki-67 [ 32 ]. However, a recent study reported that inhibition of USP7 reversely induces cell proliferation regulating SMAD3 autoregulation regardless of the p53 axis in p53-deficient lung cancer [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The role of the canonical transforming growth factor beta (TGF‐β) signaling pathway is well established in multiple physiological and pathological processes, and its constituent members include a ligand (TGF‐β1), two receptors (TGFBR1 and TGFBR2), and three SMADs (SMAD2, SMAD3, and SMAD4), which are involved in transferring extracellular TGF‐β signals to the nucleus, and regulating the expression of target genes (Du et al, 2018). Furthermore, the canonical TGF‐β signaling pathway is controlled by transcriptional regulation (Ammous et al, 2021; Wang et al, 2021), posttranscriptional regulation (Zhang et al, 2021), and PTMs (Huang et al, 2021). Among the important PTMs, ubiquitination and deubiquitination play critical roles in regulation of the TGF‐β signaling pathway in various cell types and tissues (Dupont et al, 2009; Eichhorn et al, 2012; Huang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the canonical TGF‐β signaling pathway is controlled by transcriptional regulation (Ammous et al, 2021; Wang et al, 2021), posttranscriptional regulation (Zhang et al, 2021), and PTMs (Huang et al, 2021). Among the important PTMs, ubiquitination and deubiquitination play critical roles in regulation of the TGF‐β signaling pathway in various cell types and tissues (Dupont et al, 2009; Eichhorn et al, 2012; Huang et al, 2021). The receptors and SMAD members involved in the canonical TGF‐β signaling pathway have been identified as the substrates of different E3 ubiquitin ligases and deubiquitylases (Chen et al, 2020; Li et al, 2019; Shrestha et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation